Lithium Chloride Catalyzed Asymmetric Domino Aza‐Michael Addition/[3 + 2] Cycloaddition Reactions for the Synthesis of Spiro‐ and Bicyclic α, β, γ‐Triamino Acid Derivatives. Issue 37 (17th August 2018) - Just, David; Hernandez‐Guerra, Daniel; Kritsch, Susanne; Pohl, Radek; Císařová, Ivana; Jones, Peter G.; Mackman, Richard; Bahador, Gina; Jahn, Ullrich
Abstract : Angularly and peri‐fused tricyclic pyrrolidinopyrazolines are efficiently prepared by LiCl‐catalyzed domino aza‐Michael addition‐1, 3‐dipolar cycloaddition reactions. The absolute stereochemistry is controlled in the aza‐Michael addition step, nonaflyl azide serves as effective diazo transfer reagent to the formed enolate and the resulting diazo dipole engages in the 1, 3‐dipolar cycloaddition step. The resulting tricyclic pyrrolidinopyrazolines can be easily transformed to enantiomerically enriched nonproteinogenic spirocyclic α, β, γ‐triamino acids, angularly or peri‐fused tricyclic β‐prolines or pyrimidines. The activity of the tricyclic amino acid derivatives against the hepatitis C virus was determined. Abstract : Angularly and peri‐fused tricyclic pyrrolidinopyrazolines are efficiently prepared by LiCl catalyzed domino aza‐Michael addition‐1, 3‐dipolar cycloaddition. The resulting tricyclic pyrrolidinopyrazolines can be easily transformed to spirocyclic or condensed bicyclic α, β, γ‐triamino acid derivatives.